(untitled) (Jurnal Manajemen dan Investasi (MANIVESTASI), 2021)
ABSTRACT Â The research objective is to determine the effect of the liquidity ratio (current ratio) and solvency (debt to total assets) on changes in profit in food and beverages companies listed on the IDX for the 2016-2018 period, either partially or simultaneously. The data analysis used in this study was using the SPSS for window version 23 software application. Data analysis techniques were carried out with the classical assumption test in this study including data normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis, test correlation coefficient, and multiple coefficient of determination test, as well as hypothesis testing criteria, namely partial test (t test) and simultaneous test (f test). Based on the results of the data output, it is obtained: (1) the liquidity ratio (current ratio) has a significant negative effect on changes in earnings, with a significance value of t (0.016> 0.05) and tCount < Â ttable. (2) the solvency ratio (debt to total assets) has a significant negative effect on changes in earnings l, with a significance value of t (0.141> 0.05), and tCount < Â ttable. (3) simultaneously (together) the liquidity ratio (current ratio) and the solvency ratio (debt to total assets) have an effect on changes in earnings, with a significant value of current ratio and debt to total assets (0.003 <0.05) and the value of fCount > Â ftable. Â Keywords: Current Ratio, Debt to Total Asset, Change in Profit Â Â ABSTRAK Â Tujuan penelitian adalah mengetahui pengaruh rasio likuditas (current ratio) dan solvabilitas (debt to total asset) terhadap perubahan laba pada perusahaan food and beverages yang terdaftar di BEI periode 2016-2018, baik secara parsial maupun secara simultan. Adapun analisis data yang digunakan dalam penelitian ini adalah menggunakan aplikasi sofware SPSS for window versi 23.Teknik analisis data yang dilakukan dengan uji asumsi klasik dalam penelitian ini meliputi uji normalitas data, uji multikolonieritas, uji autokorelasi, uji heteroskedastisitas, analisis regresi linier berganda, uji koefisien korelasi, dan uji koefisien determinasi berganda, serta kriteria pengujian hipotesis yaitu uji parsial (uji t) dan uji simultan (uji f). Berdasarkan hasil output data diperoleh: (1) Rasio Likuiditas (current ratio) memiliki pengaruh negatif signifikan terhadap perubahan laba, dengan nilai signifikansi t (0,016 > 0,05), dan thitung < ttabel. (2) Rasio Solvabilitas (debt to total assets) memiliki pengaruh negatif tidak signifikan terhadap perubahan laba, dengan nilai signifikansi t (0,141 > 0,05), dan thitung < Â ttabel . (3) Secara simultan (bersama-sama) Rasio likuiditas (current ratio) dan Rasio Solvabilitas (debt to tota assets) berpengaruh signifikan terhadap Perubahan Laba, dengan nilai signifikan current ratio dan debt to total assets ( 0,003 < 0,05) dan nilai Fhitung > Ftabel. Kata Kunci : Current Ratio, Debt to Total Asset, Perubahan Laba